Non-Contrast Head CT Features in HIV Patients with and without Antiretrovirals Therapy At Adam Malik General Hospital, Medan - Wibowo, Tri Widi Wibowo; Sipahutar, Henny Maisara (TALENTA Publisher, Universitas Sumatera Utara, 2025)
ABSTRACT Background: Human Immunodeficiency Virus (HIV) weakens the immune system and leads to Acquired Immune Deficiency Syndrome (AIDS). Patients may also developed cerebral toxoplasmosis. CT scans of the head without contrast can help diagnose opportunistic infections and monitor therapy response. Method: This descriptive, cross-sectional study was conducted from August 2021 to July 2022 at H. Adam Malik General Hospital, Medan. Data is presented in terms of numbers (n) and percentages (%) for variables such as age, gender, and non-contrast head CT scan images. Chi-square tests were used for bivariate analysis, with p-values <0.05 considered significant. Results: The mean age of patients receiving and not receiving ARVs was 35.0 Â± 12.83 years and 37.3 Â± 12.5 years, respectively. The majority were male. Most patients on ARVs showed no lesions on CT scans. Conclusion: Hypodense lesions were the most common findings in patients on ARVs, with multiple lesions observed in the majority of samples.